Impact of LEAP and CBT-AN Therapy on Improving Outcomes in Women with Anorexia Nervosa - Phillipa Hay; Mohammed Mohsin; Liquan Liu; Stephen Touyz; Caroline Meyer; Jon Arcelus; Sloane Madden; Evelyn Attia; Kathleen M. Pike; Janet Conti (Behavioral Sciences, 2023)
Anorexia nervosa (AN) is a mental health disorder that has serious physical, emotional and social consequences. Whilst cognitive behavioural therapy for AN (CBT-AN) has demonstrated efficacy, there remains a global need to improve AN treatment. Compulsive exercise activity therapy (LEAP) is an active therapy consisting of the addition to CBT-AN of eight specific sessions that focus on exercise and motivation for behavioural change. This paper presents a secondary analysis of 74 female participants in a randomised control trial of LEAP plus CBT-AN versus CBT-AN alone. The main aim of this study was to explore putative predictors and to estimate the magnitude of changes due to LEAP for specific outcome measures. Participants (LEAP: n = 36; CBT-AN: n = 38) were assessed at three successive surveys: baseline, end of therapy, and 6 months post-therapy. The overall effect sizes for changes between baseline to end of therapy and baseline to 6-month follow-up assessment showed large effect sizes (Cohen’s d > = 0.80) for mental-health-related quality of life (MHRQoL), weight concern, dietary restraint, eating concern, AN stage change, and psychological distress (all p < 0.05). The results also indicated that several pre-treatment characteristics, including body mass index (BMI), level of eating disorder (ED) symptoms, and MHRQoL are important for identifying whether a treatment is likely to be effective. Future treatment programs should aim to optimise early improvements in BMI, ED symptoms, and MHRQoL.